Revisiting the Past to Innovate the Future: The Mediating Impact of Absorptive Capacity on Organizational Forgetting and Innovation Performance in SME - Bongso, Gromyko; Dumonda Silitonga, Vera (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
Organizational forgetting is one of the keys to success in improving innovation performance in a business for Small and Medium Enterprises (SMEs). This study examines the direct and indirect effects of organizational forgetting on innovation performance through absorptive capacity. This study was conducted on 135 SME owners in Jakarta and Tangerang. PLS-SEM was used as the analysis method of this study. The results show that organizational forgetting plays an important role directly and indirectly in innovation performance through absorptive capacity. Absorption capacity has a significant direct effect on innovation performance. The ability of SMEs to receive information and knowledge can improve their business ability to innovate. The findings of this study indicate the importance of organizational forgetting or not learning in SMEs.